Tunable Optical Filter Based on Mechanically Induced Cascaded Long Period Optical Fiber Grating. (17th June 2013) - Ugale, Sunita P.; Mishra, Vivekanand
Abstract : We have proposed and demonstrated experimentally a novel and simple tunable optical filter based on mechanically induced and cascaded long period optical fiber gratings. In this filter variable FWHM and center wavelength is provided by cascading long period and ultralong period optical fiber gratings with different periods in a novel fiber structure. We report here for the first time to our knowledge the characterization of mechanically induced long period fiber gratings with periods up to several millimeters in novel multimode-single-mode-multimode fiber structure. We have obtained maximum loss peak of around 20 dB.